Evaluation in political discourse addressed to women: Appraisal analysis of Cosmopolitan's online coverage of the 2014 US midterm elections. (August 2017) - Aloy Mayo, María; Taboada, Maite
Abstract: Before the US midterm elections of November 2014, the well-known women's magazine Cosmopolitan decided to include politics in its contents. The editorial board stated that their aim was to encourage readers to vote and to be engaged with women's rights advocay in the election process. To that end, Cosmopolitan created a new website, CosmoVotes, with content ranging from discussion of political issues to endorsement of specific candidates who were believed to advance women's issues. Topics include labour rights, abortion, contraception, health, minimum wage and social equity. This paper evaluates the discourse of this new section of the Cosmopolitan website, together with readers' responses, concentrating on evaluative language. In particular, we are concerned with differences between the editorial position and readers' responses as viewed through the Appraisal framework (Martin and White, 2005), and the role that verbal processes play in the expression of evaluative meanings. The corpus used for the analysis consists of a selection of articles and readers' opinions from CosmoVotes . The methodology is based on annotation of Appraisal features and processes related to the interpersonal dimension of meaning. Those features reveal how attitudes are evaluated and capture ideological positionings in this discourse. Our results show that CosmoVotes has special characteristics, such as a predominance of high intensification in the readers' opinions, and strong negative judgements and expressions, while the magazine's pieces on political issues are more nuanced and eschew intensification.